Technological trends in the fashion industry and their impact on human talent - TORRES, IVAN MAURICIO
The importance of understanding the impact of technological trends in the productive sector is necessary as it will allow providing relevant and quality training to the current and new skilled workforce. This document, which arises from the bets of the Technological Plan of the Centro de Diseño Tecnológico Industrial – regional Valle, aims to validate the technological trends to prioritize its implementation in companies in the clothing sector, footwear and leather goods in the city of Cali to know its impact on human talent. The research method used is descriptive, based on the design and application of a survey sent through e-mail addressed to senior managers, coordinators/supervisors and/or heads of human talent of companies in the region. The main conclusion of the study is that companies aim to implement trends that are linked to respond to consumer preferences which are being influenced by the care and preservation of the environment.